Protein Glutathionylation and Glutaredoxin: Role in Neurodegenerative Diseases - Haseena P. A.; Latha Diwakar; Vijayalakshmi Ravindranath (MDPI AG, 2022)
Oxidative stress has been implicated in the pathogenesis and progression of many neurodegenerative disorders including Parkinson's disease and Alzheimer's disease. One of the major enzyme systems involved in the defense against reactive oxygen species are the tripeptide glutathione and oxidoreductase glutaredoxin. Glutathione and glutaredoxin system are very important in the brain because of the oxidative modification of protein thiols to protein glutathione mixed disulfides with the concomitant formation of oxidized glutathione during oxidative stress. Formation of Pr-SSG acts as a sink in the brain and is reduced back to protein thiols during recovery, thus restoring protein functions. This is unlike in the liver, which has a high turnover of glutathione, and formation of Pr-SSG is very minimal as liver is able to quickly quench the prooxidant species. Given the important role glutathione and glutaredoxin play in the brain, both in normal and pathologic states, it is necessary to study ways to augment the system to help maintain the protein thiol status. This review details the importance of glutathione and glutaredoxin systems in several neurodegenerative disorders and emphasizes the potential augmentation of this system as a target to effectively protect the brain during aging.